DETERMINANTS OF LOW BIRTH WEIGHT BABIES (LBW) IN THE UPT BOLO HEALTH CENTER, BOLO SUBDISTRICT, BIMA REGENCY, NTB IN 2018 - Nurannisa Fitria Aprianti; Kodrat Pramudho; Bambang Setiaji (UHAMKA Press, 2019)
Low birth weight babies (LBW) are still the main cause of perinatal death. The prevalence of low birth weight babies (LBW) is estimated at 15%, and Indonesia has the prevalence of low birth weight of 10.2%. The causes of infant mortality in Kabupaten Bima are mostly caused by Babies with Low Birth Weight (LBW) of (43.75%). This study aims to determine the relationship and describe the Determinants of Infants Low Birth Weight (LBW). This research was conducted at Bolo health center, Bolo Sub district, Bima Regency in March-April 2018. The research method is quantitative research equipped with qualitative research and case control was used as research design. The total population was 909 people and the sample was 180 people with a ratio of 1: 2 which was 60:80. The sampling technique uses simple random sampling. Data analysis techniques consist of univariat analysis, chi square test, and simple logistic regression test. Qualitative data analysis techniques uses in-depth interviews and FGD (Focus Group Discussion). The results of the study found that there was a significant relationship between the size of maternal LILA, BMI, maternal weight gain during pregnancy, ANC frequency, anemia and Fe consumption with LBW where the value of p is <0.05. In the multivariate analysis of simple logistic regression test, it obtained that the variable LILA size of the mother with an Exp (B) value was 19,017 (4,946-73,121) which means that the size of the mother's LILA has an effect was 19,017 times on Low Birth Weight Babies. Increase counseling on nutrition and prevention of anemia in pregnant women, socialization of reproductive health, family planning, consumption of iron and improve the quality of health services, especially inspection of ANC according to standards, improve facilities and infrastructure for health facilities and conduct training on basic LBW management by the health office and health center.